IX. Research on the Influence of Pilot Free Trade Zone on the Economic Development of Shandong Province - Liu, Baoyue; Zhang, Juyong (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
The Shanghai Pilot Free Trade Zone was China’s first of its kind, initiating the broader development of pilot free trade zones across the country. By 2023, China had established 21 such zones. 2019 Shandong Province launched its free trade area, encompassing Qingdao, Yantai, and Jinan. This region has prioritised innovation-driven development and strengthened risk prevention mechanisms to support economic growth. This paper examines the impact of the Shandong Pilot Free Trade Zone on regional economic development, focusing on gross domestic product, trade, and investment. The findings indicate that the zone has positively influenced foreign trade by expanding its volume and fostering industrial agglomeration. It has also enhanced the efficiency of foreign investment through improved investment structures and diversified financing channels. Additionally, the zone contributes to balancing the roles of the market and government and improving the tax system.